ANALISIS MANFAAT PENGIMPLEMENTASIAN BASIS DATA DI DALAM LINGKUNGAN SEKOLAH (Jurnal Riset Manajemen dan Akuntansi, 2023)
The aim of this study to provide the importance of the benefits of databases in schools today, because in this sophisticated era, database needs are needed to make it easier to make reports, retrieve and store data that was originally made manually which is time consuming and prone to data errors. . With the application of a database system, everything can be done easily and quickly, and the resulting data will be accurate. The research method used is a qualitative method by observing and recording reality through observation, interviews, and documentation. The results of the study show that the benefits of using databases in schools today are the quality of the data and information accessed according to what is input, and the most important benefit is classifying data and information so that it is easier for teachers to understand, anticipating the occurrence of data similarities or data instability. Helping the process of saving, accessing, editing, and deleting data, Protecting databases for schools to shorten processing time and get significant results